Hacker Nation: China's Cyber Assault. - Gutmann, Ethan (World Affairs)
The writer considers steps that the U.S. should take to combat Internet hacking sanctioned by the Chinese government. Evidence accumulated over the past decade shows that the Communist Party has no qualms about using a controlled Internet to threaten the West and to achieve China's strategic goals. China will only cooperate if its internally controlled Internet is threatened.